Dynamic reconfiguration of aperiodic brain activity supports cognitive functioning in epilepsy: A neural fingerprint identification - Lopez, Emahnuel Troisi; Corsi, Marie-Constance; Danieli, Alberto; Antoniazzi, Lisa; Angiolelli, Marianna; Bonanni, Paolo; Sorrentino, Pierpaolo; Duma, Gian Marco (iScience, 2025)
Temporal lobe epilepsy (TLE) is characterized by alterations of brain dynamic on a large-scale associated with altered cognitive functioning. Here, we aimed at analyzing dynamic reconfiguration of brain activity, using the neural fingerprint approach, to delineate subject-specific characteristics and their cognitive correlates in TLE. We collected 10 min of resting-state scalp-electroencephalography (EEG, 128 channels), free from epileptiform activity, from 68 TLE patients and 34 controls. The functional network was defined by the spatiotemporal spreading, across cortical regions, of aperiodic bursts of signals’ amplitude (neuronal avalanches), encapsulated into the avalanche transition matrix (ATM). The fingerprint analysis of the ATMs revealed more stereotyped patterns in patients with respect to controls, with the greatest stereotypy in bilateral TLE. Finally, indices extracted from individual patterns of brain dynamics correlated with the memory impairment in unilateral TLE. This study helped understand how dynamic brain activity in TLE is shaped and provided patient-specific indices useful for personalized medicine. [Display omitted] •Identification of patients with temporal epilepsy using non-linear part of the EEG signal•Neural fingerprint differentiates between unilateral vs. bilateral temporal lobe epilepsy•Patients with temporal lobe epilepsy are characterized by more stereotyped brain dynamics•Memory function improves in patients whose brain dynamics resemble those of controls Neurology